Near-Perfect Narrow-Band Tunable Graphene Absorber with a Dual-Layer Asymmetric Meta-Grating - Junfang Liang; Jinhua Hu; Xiuhong Liu; Jijun Zhao (Photonics, 2022)
A near-perfect narrow-band graphene-based absorber was fabricated using a resonant system integrated with an asymmetric meta-grating at a wavelength of 1550 nm. By optimizing the gap between the two grating strips, the absorption of monolayer graphene can be increased to 99.6% owing to the strong field confinement of the bottom zero-contrast grating (ZCG). The position of the absorption spectrum could be adjusted by tailoring the grating period or the thickness of the waveguide layer. Interestingly, absorption spectrum linewidth can be tailored by changing the thickness of the spacer layer. The accidental bound states in the continuum (BICs) are then demonstrated in the structure. Moreover, the designed structure realizes the dynamic adjustment of the absorption efficiency at a specific wavelength, which has excellent potential in integrated optical devices and systems.